PHYSIOTHERAPY MANAGEMENT IN CASES OF BRACHIALGIA DUE TO CERVICAL SPONDYLOARTHROSIS - Sihombing, Eka; Wooton, Ian; Mazdalifah, Nur; Sidabutar, Sondang; Wardati, Jumadiah (Universitas Efarina, 2021)
The purpose of this study was to carry out physiotherapy management in cases of brachialgia due to cervical spondyloarthrosis. This research is a study that examines physiotherapy, the examination process to determine the patient's problems begins with anamnesis, examination, and continues with determining a physiotherapy diagnosis. Anamnesis is divided into two, namely general anamnesis and special anamnesis. The results showed that cervical spondyloarthrosis is a condition of the degenerative process of the intervertebral discs and the connective tissue between the vertebrae. Degeneration causes the disc to begin to thin because its ability to absorb water decreases resulting in a decrease in water content and the matrix in the disc decreases. Spasms of the cervical muscles can also cause pain because ischemia of these muscles compresses the blood vessels so that blood flow will slow down and there is also a decrease in tissue mobility/tolerance to a stretch. All of the above factors will cause a decrease in the range of motion of the cervical joints. In this case brachialgia is caused by cervical spondyloarthrosis which affects C4, C5, C6 which causes excessive pain and tingling along the right arm, so OS requires reassurance in the form of TENS modality with the coplanar method, 2 channels, by-symm flow and using pain and sensory analgesia and US modalities and neck stretching exercises. With the hope that the pain in the shoulder and excessive tingling and tissue adhesions that OS feels are reduced.